Marlowe Presents the Greed of a Renaissance Man in Dr. Faustus - Shrestha, Muna (Nepal Journal of Multidisciplinary Research, 2022)
The aim of this present article is to analyze greed of the Renaissance man during the transitional phase between the medieval to the early Renaissance period in the development of human civilization. Christopher Marlow’s Doctor Faustus was published in 1592, where a man sells his soul to Satan for power and knowledge. It is the theme of a Renaissance man that has the desire of acquiring unlimited knowledge, individualism, free play of mind, power and pleasure. The hero of the play is at the peak of his achievement and finishes with his collapse into misery, death and damnation. So, Doctor Faustus who pursues false knowledge is given the severest penalty in the form of mental disturbance and unrest through and till the end of his life. At last, he seems to repent and regret for his actions but it is too late. Mephistopheles gathers his soul and Faustus goes with him to hell.